(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kamal I, Arrofaha N, Susila, Yulita KS, Rachmat HH, Susilowati A. 2023. Genetic variation and phylogenetic position of Taxus sumatrana (Miq.) de Laub. (Taxaceae) in Sumatra, Indonesia based on trnL-trnF region. Biodiversitas 24: 5155-5166. Taxus sumatrana (Miq.) de Laub. is a synonym of T. wallichiana Zucc. by some authors based on morphological characters and its distribution. This species is a medicinal plant and contains taxol as an anti-cancer with slow natural regeneration rate and increasing threats to their existence. This study aimed to determine the genetic diversity and the phylogenetic analysis using trnL-trnF for T. sumatrana growing in Sumatra, Indonesia. The total of 37 individuals from three natural populations of T. sumatrana were studied, consisting of the current new collection from Toba - North Sumatra and previously studied population of Dempo - South Sumatra and Sungai Penuh, Kerinci Seblat National Park - Jambi. The Toba population did not show variation at individual level within the population as similar results were obtained from the previous study. However, one indel (- and A) was found at 217 bp from all three T. sumatrana populations from Sumatra, Indonesia. When the sequences were aligned with the reference sequence from GenBank, single base substitutions were found at 344, 478,722, and 757 bp consisting of one indel and three single nucleotide polymorphisms (SNPs). Phylogeny tree showed that T. sumatrana from Sumatra population clustered together with T. mairei and T. wallichiana var. mairei and later combined with other T. sumatrana available in NCBI.